U.S. Agricultural Colleges’ International Strategic Partnerships:: Leadership’s Critical Insights and Recommendations - Lacy, William; Merilus, Jean-Yves; Liu, Xiaoguang; Lacy, Laura R. (The International Journal of Sociology of Agriculture and Food, 2021)
Historically, U.S. colleges of agriculture have been leaders in generating, disseminating, and applying the latest science to address the needs of society, in educating the next generation of professionals and leaders, and in engaging in international partnerships. As these processes and goals become more global, strategic international partnerships become more critical. To understand how college leaders are approaching these critical relationships, deans of 33 leading U.S. colleges of agriculture were surveyed on key aspects of their international partnerships. The most frequently identified major goals were: ‘enhancing the quality of research and scholarship’; and ‘strengthening students’ education’.  However, more than half the deans noted four challenging issues for realizing productive partnerships: ‘difference in educational quality and standards among partners’; ‘incongruent expectations between the institutions’; ‘language and cultural differences’; and ‘different levels of institutional commitment’. Fewer than half the deans indicated that dedicated resources were allocated for the partnerships. Ten critical topics often identified by college strategic plans were seen by most of the deans as important for their college but not nearly as important for their international partnerships. Three quarters of the deans identified seven factors for future successful international partnerships, including: ‘leadership at the program and college level’; and ‘adequate resources, including funding, eligible faculty, facilities and space’.  Several future research needs were identified: international strategic partnerships will require informed and creative college leadership and likely need to expand in scale, scope, diversity and complexity, draw successfully on the scientific knowledge worldwide, and carefully consider the wide, unique opportunities and challenges of these partnerships.